Induction to tetraploidy in Pacific oysters (Crassostrea gigas) - Melo, Emílio Mateus Costa; Sühnel, Simone; Silva , Francisco Carlos da; Melo, Claudio Manoel Rodrigues de (Acta Scientiarum. Animal Sciences, 2022)
As an alternative to the use of cytochalasin B (CB), 6-dimethylamino-purine (6-DMAP) and thermal shock (heat shock by increasing the temperature from 25 to 36ºC) could be used to induce tetraploidy in Pacific oyster (Crassostrea gigas) diploids. Induction was performed by applying shocks after elimination of the first polar corpuscle at the end of meiosis I. Ploidy rates were verified using flow cytometry. Tetraploid larvae were obtained using all inductor (6-DMAP, thermal shock and CB) treatments. No difference in the efficiency of tetraploidy induction was noted among 6-DMAP, thermal shock and CB. The number of D-larvae and their yield, determined by calculating the percentage of well-formed D-larvae in relation to the total number of larvae, was similar (p > 0.05) among the evaluated induction methods. We suggest that 6-DMAP and thermal shock should be used in tetraploidy induction protocols, thereby avoiding the use of CB, which is a harmful agent for both humans and the environment.